Servant Leadership Kepala Sekolah Dalam Implementasi Kurikulum Merdeka di SMA Negeri 1 Muaro Jambi - Serlly Serlly; Sofyan Sofyan; Agus Lestari (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine two main aspects of the principal's servant leadership in the implementation of the Independent Curriculum at SMA Negeri 1 Muaro Jambi, namely: the application of servant leadership principles in supporting the implementation of the Independent Curriculum at SMA Negeri 1 Muaro Jambi and the challenges faced by the principal in implementing the Independent Curriculum through a servant leadership approach. This study employs a qualitative method with a phenomenological approach. Data collection techniques include interviews, observations, and document analysis. The informants in this study consist of the principal, vice principals, subject teachers, and student representatives. The findings of the study reveal that: (1) the principal applies servant leadership principles based on five indicators. The principal actively supports teachers and students through mentoring, training, and creating a conducive learning environment. Servant leadership has been proven to help teachers adapt to curriculum changes, enhance collaboration, and strengthen teacher and student motivation in implementing the Independent Curriculum. (2) However, there are several challenges in implementing the Independent Curriculum through a servant leadership approach, including teachers' limited understanding of the curriculum, difficulties in accepting change, inadequate technological support, and varying levels of teacher adaptation to the Independent Curriculum.